Animals as Criminal Evidence in the Perspective of Criminal Procedure Law - Lievia Wijaya, Yuan; Zuhdi, Syaifuddin (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
This study aims to determine the conception of living things as evidence in a criminal offense based on existing legal regulations in Indonesia; the method used in this research is a normative method with a statutory approach, and the data used is secondary data, in the form of primary legal materials onsisting of Law Number 8 of 1981 concerning Criminal Procedure (KUHAP) and the Draft Criminal Procedure Code (RKUHAP). The results of this study found that living things can be used as evidence if they meet several leading indicators, one of which is that these living things must be directly related to a criminal case; the novelty of this research regards the wetting and comparison of animals as evidence from the perspective of the Criminal Procedure Code and Draft Criminal Procedure Code.